Determinación del costo de prestación de los servicios del registro municipal automotor en el Consorcio Tránsito Palmira mediante la metodología de costos basados en actividades ABC (2021)
The Palmira transit consortium is a private entity, specialized in the provision of transit and mobility services, corresponding to the registers of motor vehicles, offenders, drivers, including the supply of software, hardware, physical adaptations, furniture and fixtures, as well such as the provision of contact center services associated with such records.